New trends on brazilian school psychology - Wechsler , Solange (1993)
The purpose of this study was to define a profile for Brazilian school psychologists. The sample consisted of participants of the 1st National Conference on School Psychology, which occured in Valinhos (São Paulo) in November/1991.One hundred thirty-ninepersons, (130 women, 9 men) answered a questionaíre comprising the professional experiences, as well as evaluation son the importance of practical as well as theoretical contents related to the development of school psychology. Results indicating the existence of a new path in Brazilian school psychology, emphasizing grupal strategies instead of individuais ones, prevention models more than intervention practices. New disciplines as well as the in-depth study of existing ones for the psychology undergraduate curriculum were proposed, based on the experiences of those professional who have been practicing for several years.